2006
DOI: 10.1111/j.1600-0404.2006.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Raised prolactin levels in myasthenia gravis: two case reports and a study of two patient populations

Abstract: There is an association of MG with raised levels of PRL in women. PRL has stimulating effects on immune activation and the increased levels might thus be implied in the pathophysiology of MG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The description of the stimulative effect of PRL on the autoimmune activation of MG was first reported by Cahill et al in 1980 [1, 6]. This was followed by Tsinzerling et al in 2006 who reported two case reports and a cohort study discussing the relationship between the severity of MG and serum PRL levels [1, 7, 8]. In 2013, Harris et al discussed the role of PRL and its potential therapeutic use for MG in the future [1, 8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The description of the stimulative effect of PRL on the autoimmune activation of MG was first reported by Cahill et al in 1980 [1, 6]. This was followed by Tsinzerling et al in 2006 who reported two case reports and a cohort study discussing the relationship between the severity of MG and serum PRL levels [1, 7, 8]. In 2013, Harris et al discussed the role of PRL and its potential therapeutic use for MG in the future [1, 8].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence demonstrates a bi-directional relationship between immune functions and the neuroendocrine system. Many in vitro and animal studies described an important role of GH in the regulation of the immune system as it stimulates T and B cells proliferation and immunoglobulin synthesis [7, 8, 12]. It is important to note that the combination of these two diseases can be a mere coincidence.…”
Section: Discussionmentioning
confidence: 99%
“…Cahill et al published the first description of the stimulating effect of PRL on the autoimmune activation of MG in 1980. 7,8 Then, in 2006, Tsinzerling et al reported two case reports and a cohort research examining the correlation between serum PRL levels and the severity of MG. [7][8][9] The function of PRL and possible therapeutic applications for MG were discussed by Harris et al in 2013. 7,9 The differential diagnosis of neurological symptoms in individuals with macroprolactinoma should be considered as MG, according to Zoli et al in 2018.The literature is clear on the frequent link between endocrine dysfunction and myasthenia.…”
Section: Case Reportmentioning
confidence: 99%